Sabahan Satay Sdn Bhd - Pg Alimuddin, Pg Muhammad Zayd Iddin; Akmadis, Mohd Suhaidi; Sukarno, Jubaidah; Monib, Nur Shukriyah; Abdul Mutalib, Nurul Shafika (2014)
The name of our company is SABAHAN SATAY SDN BHD is a business that provides frozen food product to the consumer. For example, frozen chicken satay and frozen beef satay. Our main office is located at lnanam, 88450, Kota Kinabalu. We expect to start up our business on 1st January 2014. The future aiming for our business is to market the product locally in Sabah. This is because people would look for a frozen satay to be cooked on the beach and their houses for any celebration or event. On the other hand, the domestic people like to eat chicken and beef satay. We are prospecting to increase 2 % and 4 % sales of our business on second and third year respectively.